Ship entering floating dock Chaguaramas Bay - Marshall (Waterman, [Trinidad and Tobago], 2011)
This postcard shows a ship entering a floating dock on Chaguaramas Bay, Trinidad. Floating docks are used to construct or carry out maintenance or repairs on any type of watercraft such ships or boats. This postcard, postmarked 1914, is addressed to Mr. George Konchakje of New York, United States of America and is a penny Trinidad postage stamp.
Colour: Sepia with hues of green; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Dry docks; Ships; 1914